Impact of a Whole-Room Atomizing Disinfection System on Healthcare Surface Contamination, Pathogen Transfer, and Labor Efficiency. (17th February 2021) - Reynolds, Kelly A.; Sexton, Jonathan D.; Garavito, Fernanda; Anderson, Brandie; Ivaska, Joan M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Healthcare surfaces contribute to nosocomial disease transmission. Studies show that despite standard guidelines and practices for cleaning and disinfection, secondary infection spread among healthcare workers and patients is common in ICUs. Manual terminal cleaning practices in healthcare are subject to highly variable results due to differences in training, compliance, and other inherent complexities. Standard cleaning practices combined with no-touch disinfecting technologies, however, may significantly lower nosocomial infection rates. The objective of this study was to evaluate the efficacy of a whole-room, no-touch disinfection intervention to reduce the concentration and cross-contamination of surface bacteria when used in tandem with manual cleaning protocols. Design: Bacterial tracers were seeded onto hospital room surfaces to quantitatively evaluate the efficacy of manual terminal cleaning practices alone and in tandem with a no-touch, whole-room atomization system. Cross-contamination potentials and labor efficiency were also evaluated. Subjects and Intervention: Environmental service personnel cleaning efficacy was evaluated pre and post application of manual terminal cleaning protocols alone and in tandem with a whole-room atomization system with an United States Environmental Protection Agency-registered hospital-grade hypochlorous acid disinfectant. Setting: The study was conducted in an unoccupied patient room at Banner University Medical Center in Tucson, AZ. The room was located in a newly constructed ICU suite. Measurements and Main Results: Manual terminal cleaning averaged a 2.4 log10 reduction in seeded bacterial counts compared with a 4.9 average and up to a 6 log10 reduction with tandem cleaning. Cross-contamination among surfaces following terminal cleaning alone was documented in 50% of the samples compared with 0% with tandem cleaning, with the latter achieving a 64% improvement in manual labor efficiency. Conclusions: The use of whole-room atomized disinfection with terminal cleaning protocols lowered manual labor times, improved disinfection outcomes, and eliminated the transfer of bacterial pathogens in healthcare environments.